Reliability of Zepp baseball on batting velocity / Raja Nurul Jannat Raja Hussain … [et al.] - Raja Hussain, Raja Nurul Jannat; Kee, Kang Mea; Mohd Razman, Rizal; Ismail, Shariman Ismadi; Shari, Maisarah; Mohd Idris, Norizzati; Abdul Razak, Rozella; Mohamed Kassim, Nur Atikah (Faculty of Sport Science and Recreation, Universiti Teknologi MARA, 2019)
In baseball and softball sports, one of the important characteristic of a successful hitter is having a fast bat swing velocity. Therefore, it is crucial to measure changes of batting velocity in training and during competitive matches. This paper quantifies the reliability of a small wearable sensor that was designed to be used in baseball and softball sports. An inertial measurement unit (IMU) manufactured by Zepp Lab, USA was used to measure the batting velocity in softball. A single female collegiate softball player completed sixty tee swings of two pre-determined swing velocities. Results from moderate velocity Vm (25.5 ± 3.5 m/s), and fast velocity range Vf (34.5 ± 3.5 m/s) were obtained. Data were collected concurrently with a 3- Dimensional (3D) motion analysis system (Qualisys Motion Capture). The reliability of the IMU was determined based on the Pearson Correlation and Intraclass Correlation (ICC) values between the IMU and the 3D data. Results indicated strong and moderate correlation between the IMU and the 3D data (Vm, r = 0.89; Vf, r = 0.59). The ICC for Vm (0.89) showed strong agreement, while fair agreement showed for Vf (0.37). However, for a total of sixty swings of two different velocities showed almost perfect agreement (ICC = 0.94). These results indicate that the Zepp Baseball device has an acceptable level of reliability in measuring batting velocity during different swing velocity ranges and it is suitable to be use in a softball-related research environment.